2020
DOI: 10.11648/j.sjc.20200803.12
|View full text |Cite
|
Sign up to set email alerts
|

Antisalmonellal Activities of Extracts, Fractions, Compounds and Semi-synthetic Flavonoid Derivatives from <i>Tristemma hirtum</i> P. Beauv (Melastomataceae)

Abstract: The development and spread of resistance to currently available antibiotics is a major drawback in the treatment of microbial infections. Salmonellosis for example remains among the most common cause of morbidity and mortality in developing countries. This study aimed to evaluate the antisalmonellal potential of extracts, fractions, isolated compounds and semi-synthetic flavonoids from Tristemma hirtum P. Beauv. Bioguided fractionation by column chromatography of the EtOAc and n-BuOH fractions led to the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The results of this work indicate that all the studied plant extracts contain steroids and phenols such as flavonoids and tannins. In comparison to our results, bioguided fractionation of the MeOH extract of T. mauritianum aerial parts led to the identification of luteolin-3′-O- β -D-glucuronopyranosyl butyl ester, quercetin-3-O- β -D-glucuronopyranosyl butyl ester, arjunolic acid-28- β -D-glucopyranosyl ester (Arjunglucoside II), asiatic acid-28- β -D-glucopyranosyl ester (Quadranoside IV), β -sitosterol, oleanolic acid, ellagic acid, casuarinine, luteolin, pterocaryanin C, quercetin-3-O- β -D-glucopyranoside, and 6-hydroxyapigenin-7-O- β -D-glucopyranoside [ 39 ]. Other study has found that T. mauritianum extract possesses significant quantities of phenols and flavonoids [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this work indicate that all the studied plant extracts contain steroids and phenols such as flavonoids and tannins. In comparison to our results, bioguided fractionation of the MeOH extract of T. mauritianum aerial parts led to the identification of luteolin-3′-O- β -D-glucuronopyranosyl butyl ester, quercetin-3-O- β -D-glucuronopyranosyl butyl ester, arjunolic acid-28- β -D-glucopyranosyl ester (Arjunglucoside II), asiatic acid-28- β -D-glucopyranosyl ester (Quadranoside IV), β -sitosterol, oleanolic acid, ellagic acid, casuarinine, luteolin, pterocaryanin C, quercetin-3-O- β -D-glucopyranoside, and 6-hydroxyapigenin-7-O- β -D-glucopyranoside [ 39 ]. Other study has found that T. mauritianum extract possesses significant quantities of phenols and flavonoids [ 25 ].…”
Section: Discussionmentioning
confidence: 99%